Moral Considerability: Ethical Foundation of the Recognition of Nature as Subject of Law - Vallejo, Santiago (2019)
In recent years, the idea of endowing rights to nature has become recurrent, which can be seen through an increasing number of theoretical analysis from different outlooks. Its study, therefore, has turned somehow mandatory in the realm of ethics, being even justified as an alternative to cope with the current environmental crisis. An ethical perspective should be assumed as an indispensable source for a theoretical and legal construction of the doctrine of rights of nature, given that great part of law-making in matters of legal status is often derivative from moral philosophy. In essence, as Stone magisterially suggests, the interconnectedness between the conferral of [fundamental] rights to new subjects of law and the concomitant expansion of the frontiers of moral standing towards themselves responds to a parallel history. Namely, holders of rights are usually deservers of moral standing. The present article encompasses this historical interrelation, briefly describing the different ethical interpretations, derived over time. The common thread running within this essay will be professor Callicott’s categorization.